2020
DOI: 10.1177/2192568220962440
|View full text |Cite
|
Sign up to set email alerts
|

Can Acupuncture Improve Chronic Spinal Pain? A Systematic Review and Meta-Analysis

Abstract: Study Design: Systematic review and meta-analysis. Objective: To investigate the effect and safety of acupuncture for the treatment of chronic spinal pain. Methods: MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, the WHO Clinical Trial Registry, and the US National Library of Medicine clinical trial registry were searched from January 1, 2000, to November 1, 2019. Randomized controlled trials (RCTs) involving patients with chronic spinal pain treated by acupunctur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…Using our inclusion criteria, no studies on dry needling were identified cluded studies (n = 10) used acupuncture for treatment of sciatica and are out bles 3 and 4. The inclusion criteria for patients with sciatica varied across the s studies included participants with sciatica symptoms and clinical findings tha with MRI or CT confirmation of lumbar disc herniation [22,[38][39][40][41]. Three stud patients with a clinical diagnosis of sciatica based on nerve root pain and re [24,42,43].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using our inclusion criteria, no studies on dry needling were identified cluded studies (n = 10) used acupuncture for treatment of sciatica and are out bles 3 and 4. The inclusion criteria for patients with sciatica varied across the s studies included participants with sciatica symptoms and clinical findings tha with MRI or CT confirmation of lumbar disc herniation [22,[38][39][40][41]. Three stud patients with a clinical diagnosis of sciatica based on nerve root pain and re [24,42,43].…”
Section: Resultsmentioning
confidence: 99%
“…According to the most updated review, Huang et al reported that for patients with sciatica, acupuncture showed favorable reduction in pain intensity at immediate weeks) follow up (weighted mean difference (WMD) −11.94, 95% confidence interval (CI) −13.22 to −10.67, I 2 0%). In addition, significant reduction in pain was demonstrated at short-term (<3 months) (WMD −8.90, CI −17.28 to −0.52, I 2 84.4%), med-term (3–6 months) (WMD −17.80, CI −19.51 to −16.60, I 2 93.0%), and long-term (>6 months) (WMD −17.60, CI −19.23 to −15.97, I 2 0%) follow ups (moderate quality evidence) [ 40 ]. Included studies for sciatica all favored acupuncture for pain compared to physical therapy, electrotherapy, and sham acupuncture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low back pain (LBP) is one of the most frequently reported complaints. Several studies point to acupuncture’s effectiveness in treating chronic spinal pain, which, besides low back pain, includes cervical and sciatic pain [ 95 , 123 , 124 ]. In this field, Molsberger et al (2002) performed a large, methodologically rigorous double-blinded trial to assess two questions: Can acupuncture contribute as an adjunctive therapy to the conservative management of LBP?…”
Section: Acupuncture Moxibustion and Cuppingmentioning
confidence: 99%